The Adoption Process to Technology Biosecurity and Vaccination in the Dispersal of Foot and Mouth Disease Bone Regency, South Sulawesi Province - Rismayanti Rismayanti (Journal of Global Innovations in Agricultural Sciences)
Adopting biosecurity and vaccination technology is one of the steps that can be taken to overcome and minimize FMD disease in beef cattle farming. This study aims to analyze the farmer's adoption of biosecurity and vaccination technology in the spread of FMD. The research was conducted from November to December 2023 in Bone Regency, South Sulawesi Province. The sample size was 99 farmers whose animals were infected or not infected with FMD. Data collection methods began with observation and interviews using a questionnaire. The data analysis used was qualitative descriptive analysis using a rating scale. Research variables in the adoption process include knowledge, persuasion, decision, implementation, and confirmation. The results showed that the technology adoption process at the knowledge stage was categorized as moderate, the persuasion stage was categorized as high, the decision stage, the implementation stage, and the confirmation stage were categorized as moderate. The average difference from the stages of the technology adoption process of implementing biosecurity and vaccination as a whole is categorized as moderate with a score of 2.15. Keywords: Adoption technology, biosecurity, breeders, disease, vaccination, Bone Regency, farmer adoption.